Changes in anthocyanins and volatile components of purple sweet potato fermented alcoholic beverage during aging. (October 2017) - Li, Suhong; An, Yingfeng; Fu, Weina; Sun, Xiao; Li, Wenjie; Li, Tuoping
Abstract: Purple sweet potato was fermented into alcoholic beverage. By using LC-MS analysis, 12 types of anthocyanins were found in the purple sweet potato alcoholic beverage (PSPFAB); these were based on cyanidin and peonidin as aglycones. The anthocyanins in young PSPFAB mainly consisted of acylates. The acylated anthocyanins, however, degraded gradually with aging. Cyanidin 3-sophoroside-5-glucoside and peonidin 3-sophoroside-5-glucoside were found to be major anthocyanins in the PSPFAB after two years of aging. Moreover, 52 kinds of volatile components were detected in PSPFAB by GC–MS analysis. Alcohol and ester substances constituted a major proportion of these volatile components of PSPFAB. After two years of aging, levels of high-alcohols such as 1-pentanol remarkably decreased to below the detection limit, while the level of total esters increased significantly. Such variation of aromas enriched and improved the flavor of PSPFAB. Graphical abstract: Highlights: Cyanidin and paeonidin were major aglycones of anthocyanins in purple sweet potato fermented alcoholic beverage. Acylated anthocyanins degraded gradually with aging process. Ester components increased significantly after aging.